The elemental composition of Stradivari's musical instruments: new results through non‐invasive EDXRF analysis. (28th December 2017) - Rovetta, T.; Invernizzi, C.; Licchelli, M.; Cacciatori, F.; Malagodi, M.
Abstract : During recent decades, many researchers have tried to understand the main influences on the extraordinary sound and beauty of the masterpieces made by the ancient violin makers. This is still a challenge for many others today. Mainly because of a lack of written historical documents, the rediscovery of some of the ancient violin‐making processes was made possible thanks to scientific analyses performed on their materials by means of diagnostic techniques. However, understanding which substances were adopted is a very hard task, because the analyses are influenced by many factors: for example, alterations, wear, retouches, and the heterogeneity of materials. This paper presents some new EDXRF results collected on eight‐stringed musical instruments made by Antonio Stradivari between 1669 and 1734 ("Clisbee" 1669, "Hellier" 1679, "Ford‐Rougemont" 1703, "Joachim‐Ma" 1714, "Russian Federation" viola 1715, "Cremonese" 1715, "Vesuvius" 1727, and "Scotland" 1734) and now preserved at the Museo del Violino in Cremona. A brief comparison with a modern violin made by Simone Ferdinando Sacconi ("Hellier copy" 1941), one of the most eminent violin makers of the 20th century and one of the greatest experts on Stradivari's work, is also provided. This represents the first comparative analysis of a wide number of ancient musical instruments made by the same violin maker over an extended period. A non‐destructive and non‐invasive approach was followed to (a) understand the elemental composition differences between the best conserved and most worn‐out surfaces; (b) check if there are elemental similarities among the finishing materials of violins made in different years by the same violin maker; (c) give new suggestions about the materials used. To distinguish the best conserved areas from the worn‐out ones, a preliminary investigation by UV‐induced fluorescence photography was performed. In addition, stereomicroscopic observations and Fourier transform infrared spectroscopy (FTIR) analyses were performed on selected areas to validate the hypotheses. The results, in some cases comparable with previous research on Stradivari instruments, have increased the pool of information about materials and treatments adopted in the Stradivari workshop.